2020
DOI: 10.1186/s12890-019-1043-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum Krebs von den lungen-6 as a diagnostic marker in connective tissue disease associated with interstitial lung disease

Abstract: Objectives: The purpose of this study was to evaluate the value of serum krebs von den lungen-6 (KL-6) level as a diagnostic indicator for connective tissue disease associated with interstitial lung disease (CTD-ILD). Methods: One hundred fifty five patients with newly diagnosed CTD in our hospital were enrolled and divided into two groups by their ILD manifestations, the CTD-ILD group and the CTD group. In parallel, 61 patients with pulmonary infection and 60 cases of healthy subjects were also enrolled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…The CA 15.3 has been previously described as alternative marker for KL-6 fibrotic lung disease 33 , a mucin-like glycoprotein mainly expressed on the type II alveolar epithelial cell surface 34 and as marker of pulmonary fibrosis 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA 15.3 has been previously described as alternative marker for KL-6 fibrotic lung disease 33 , a mucin-like glycoprotein mainly expressed on the type II alveolar epithelial cell surface 34 and as marker of pulmonary fibrosis 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Kl-6 is recognized as a prognostic biomarker of Interstitial Lung Disease (ILDs), predicting response to antifibrotic therapies 33 , 37 , 38 , has been correlated with risk of mortality in Acute Respiratory Distress Syndrome (ARDS) 39 and reported as indicator of alveolar epithelial cell damage induced by mechanical ventilatory support 39 . High peripheral levels of this protein have also been reported in Legionella, Pneumocystis jivorecii infections 40 , 41 and measles‐associated pneumonia 42 , as well as in viral pneumonia 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The disruption in the alveolar epithelium causes leakage in the basement membrane, which later enhances the permeability of the lung vasculature, resulting in the increase of serum KL-6 level. Therefore, the level of serum KL-6 may represent the extent of lung damage in COVID-19 patients [5,10] . A case report of two COVID-19 patients by Nakamura et al [27] showed a difference in serum KL-6 level, which later both cases were defined as different primary "phenotypes" of COVID-19 patients, [16] 0.83 (0.52-0.98) Awano et al, 2020 [11] 0.76 (0.53-0.92)…”
Section: Selectionmentioning
confidence: 99%
“…The severity of lung injury in certain diseases or conditions may be reflected in the serum KL-6, a glycoprotein mainly expressed on type II alveolar epithelium cells [5] . Its role in lung diseases has been observed in rheumatoid-related interstitial lung disease, idiopathic interstitial pneumonia, acute exacerbation in idiopathic pulmonary fibrosis, lung cancer, and connective tissue-related interstitial lung disease [5][6][7][8][9] . Some studies have also shown that the severity of COVID-19 patients is reflected through the higher KL-6 levels in the blood, thus indicating type II pneumocyte damage and lung injury [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…16 Some studies have investigated serum KL-6 as a useful biomarker to assess ILD in SSc patients as well as a disease activity marker. [17][18][19][20] As no data are available on KL-6 concentrations in patients with SSc-ILD associated with PPFE, this study undertook to compare serial changes in KL-6 in SSc-ILD patients with and without PPFE, in order to verify its prognostic value as a disease biomarker.…”
Section: Introductionmentioning
confidence: 99%